Wheat Yield Differences between Two Cropping Systems in Permanent Raised-Beds as Affected by Components of Nitrogen Use Efficiency. Issue 8 (28th April 2017) - Limon-Ortega, Agustin
ABSTRACT: Permanent raised-bed is an alternative planting system for wheat (Triticum aestivum L.) in rain-fed areas. However, this system in monoculture conditions produces lower yields compared with wheat in rotation. Our objective was to estimate these yield differences as affected by nitrogen (N) use efficiency (NUE). Wheat in monoculture and in rotation with maize ( Zea mays L.) was evaluated for eight years (2002–2009) with four N rates (0, 40, 80 or 120 kg ha −1 ). Yield response to N in monoculture was consistently lower than for wheat in rotation. Yield reduction in monoculture at low and high N rate was 81 and 99% attributed to NUE out of which 70 and 82% was due to the uptake efficiency (UPE) and 30 and 19% to the utilization efficiency (UTE), respectively. Total N uptake proved to be the parameter that needs to be improved to enhance wheat yield in monoculture. Abbreviations: NUE: nitrogen use efficiency; UPE: uptake efficiency; UTE: utilization efficiency; Ns: nitrogen supply; NDVI: normalized difference vegetation index